Optimization of a fast and simple method for the determination of Ethanol in gel by Hydrogen Nuclear magnetic resonance - Mahmoud, Talal Suleiman; Meyer, Alexandre Robison; Netto, Pedro Toledo (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Due to the COVID-19 pandemic, the use of alcohol-based sanitizers was intensified, resulting in the need for its monitoring. The most common techniques for determining the ethanol content are gas chromatography, spectrophotometry and alcoholometry, which are predominantly used for liquid solutions. NMR is one of the most important qualitative analysis technologies, however, it is rarely used for quantitative purposes such as the analysis of samples containing ethanol in gel. In this work, we proposed two methods for quantifying the ethanol content in gels using quantitative Hydrogen Nuclear Magnetic Resonance (1H qNMR) spectroscopy. The quantification methods by external standardization and by standard addition showed selectivity, good linearity, good accuracy and precision with recoveries between 99 and 107% and coefficient of variation from 0.09 to 4.35% respectively, in accordance with the validation guidelines in chemical analysis. The 1H qNMR optimized and validated in this work allowed the use of both methods in commercial samples of ethanol in gel. The external standardization method is the most recommended by the authors for being simpler and faster.